The total plate count of beras kencur herbal medicine in sub-district market Tulungagung city - Eka Puspitasari; Chalies Diah Pratiwi; Tri Wahyuni (Medical Laboratory Analysis and Sciences Journal, 2019)
Herbal medicine is a traditional drink made from natural ingredients for human health and is made with methods and equipment that are easier in its simplicity which often does not pay attention to hygiene factors and can be a medium for disease transmission. Based on the Regulation of the Head of the Republic of Indonesia Drug and Food Control Agency No. 12 of 2014 concerning requirements for drug fluids in the form of microbial contamination / ALT ≤104 colonies/ml. The purpose of this study was to study the estimated numbers of traditional herbs sold in the Tulungagung District market. The research design used is descriptive. The sampling technique uses a total sampling technique of 6 samples from 4 different markets. Sample meeting with the ALT method in May 2018 in the microbiology laboratory of STIKes Hutama Abdi Husada Tulungagung. The results of the study found that three out of six samples of traditional herbal medicine of kencur rice exceeded the microbial contamination threshold with an average yield of 1 x 107 CFU / ml. The study concludes is that 50% of the sample is not suitable for consumption and 50% of the sample is suitable for consumption. This requires Regulation of BPOM RI Number 12 the year 2014 Regarding Quality Requirements for Traditional Medicines, namely ≤104 colonies/ml. Herbal traders need to pay attention to raw materials, processing, equipment, air used, and containers used.